2022
DOI: 10.1149/ma2022-024532mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of 2D Materials - Quaternary Derived Nanostructures - and Their Polysulfide Anchoring Capabilities in Lithium Sulfur Batteries

Abstract: Metal-sulfur battery chemistries have garnered a lot of interest due to their 5-10 fold higher theoretical energy densities compared to state-of-the-art lithium-ion batteries, in addition to the abundance and environmental benignity of sulfur. However, the insulating nature of sulfur, the formation and shuttling of polysulfides, are still major drawbacks. In this work we started with quaternary ammonium salts or quat derived nanostructures (QDNs), synthesized using a facile bottom-up reaction, directly from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a follow up paper, we showed that this prolonged stability could, in part, be attributed to the polar‐polar interactions with the NFs’ hydroxylated surfaces with polysulfides as confirmed by post‐mortem XPS analysis. [ 37 ]…”
Section: D Lepidocrocite Titanate Nanofilaments 1dlsmentioning
confidence: 99%
“…In a follow up paper, we showed that this prolonged stability could, in part, be attributed to the polar‐polar interactions with the NFs’ hydroxylated surfaces with polysulfides as confirmed by post‐mortem XPS analysis. [ 37 ]…”
Section: D Lepidocrocite Titanate Nanofilaments 1dlsmentioning
confidence: 99%
“…24 We have already shown that 1DLs can be used for a large host of applications. They can be used as electrodes in lithiumion and lithium− sulfur batteries, 21,34 photochemical hydrogen production, 35 chemical cancer therapies, 21 water purification, 24 dye degradation, 25 polymer composites, 36 and perovskite solar cells. 37 Compared to the other CO 2 capturing materials, the 1DLs have several advantages.…”
Section: T H Imentioning
confidence: 99%
“…12 The authors reported good performance as an electrode for lithium-ion and lithium−sulfur batteries and an ability to reduce the viability of cancer cells. 12,48 At 4.1 eV, the band-gap energy, E g , of the resulting flakes is one of the highest, if not the highest value ever reported for titania-based nanostructures as a result of quantum confinement. 13 Despite the E g , the flakes' electronic band structure possessed visible light absorbance that was attributed to mid-band-gap energy states.…”
Section: ■ Introductionmentioning
confidence: 97%